1988
DOI: 10.1111/j.1365-2265.1988.tb02888.x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Polycystic Ovarian Disease by Inducing Ovulation With Pulsatile Subcutaneous Administration of Human Menopausal Gonadotrophin Associated With Luteinizing Hormone‐releasing Hormone Analogue

Abstract: Treatment with a combination of luteinizing hormone-releasing analogue (GnRHa, Buserelin) and pulsatile administration of hMG (Group I) were used to induce ovulation in nine patients with polycystic ovary syndrome (PCO). The same patients were also treated with pulsatile hMG administration alone (Group II). Ovulation was observed in all twelve treatment cycles in Group I, and there were two pregnancies. In Group II, ovulation occurred in 22 of 26 treatment cycles. Ovarian hyperstimulation occurred in one cycle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1990
1990
1995
1995

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…Pulsatile subcutaneous administration of hMG has been shown to be effective in inducing follicular matura tion and ovulation in patients with various types of an ovulatory infertility [7,10,13]. The present study has also demonstrated a high rate (89.2%) of ovulation induction with pulsatile administration of hMG or FSH in patients with PCOS.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…Pulsatile subcutaneous administration of hMG has been shown to be effective in inducing follicular matura tion and ovulation in patients with various types of an ovulatory infertility [7,10,13]. The present study has also demonstrated a high rate (89.2%) of ovulation induction with pulsatile administration of hMG or FSH in patients with PCOS.…”
Section: Discussionsupporting
confidence: 55%
“…The administration of Buserelin resulted in continued suppression of serum LH and FSH following the initial rise [10,15]. Fleming et al [15,16] demonstrated that the characteristics of ovarian responsiveness to exoge nous gonadotropins were unchanged after suppression of LH with Buserelin in patients with PCOS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation